2019
DOI: 10.1186/s12883-019-1265-y
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome in end stage renal disease patients undergoing hemodialysis

Abstract: Background The prevalence of Restless legs syndrome (RLS) in End Stage Renal Disease (ESRD) patients is higher than that in the general population. However, the associations of RLS within the ESRD population are inconsistent and RLS is usually neglected in dialysis centers, although it impairs the life quality among ESRD patients. We aim to investigate the prevalence of RLS in patients with ESRD undergoing maintenance hemodialysis and evaluate the risk factors of developing RLS and the effect of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 42 publications
1
36
4
3
Order By: Relevance
“…In addition; age and co-morbidity as diabetes mellitus were associated with severity of RLS symptoms. Also this study is contradicting with Lin , Zhang , Qiu , Ni , Yu , Ku , Ondo , Yu and Wu (2019), who reported that RLS is more frequent in female gender with end stage renal disease; so the correlation between biosocio-demographic characteristics still contentious.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…In addition; age and co-morbidity as diabetes mellitus were associated with severity of RLS symptoms. Also this study is contradicting with Lin , Zhang , Qiu , Ni , Yu , Ku , Ondo , Yu and Wu (2019), who reported that RLS is more frequent in female gender with end stage renal disease; so the correlation between biosocio-demographic characteristics still contentious.…”
Section: Discussioncontrasting
confidence: 92%
“…This results is consistent with Kaur, Venkateasan, Kaur, Rawat, Massey(2016), who revealed that; no significant association between the pre RLS rating scale score with personal characteristics as sex, age, type of family, level of education, marital status, occupation, religion, frequency of dialysis per week, and duration of dialysis per cycle, except income and personnel habits. Also; Lin , Zhang , Qiu , Ni , Yu , Ku , Ondo , Yu and Wu (2019) found no meaningful association between RLS and the period of hemodialysis. The present results also supported by (Salman, 2011), who concluded that; RLS wasn't significantly correlated to age, and there was no significant difference in sex or duration of dialysis between the study participants.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies showed that RLS occurred in 12% to 62% of dialysis patients [6][7][8][9], and higher incidence rates of RLS among dialysis patients have been reported in studies outside Japan. This may be attributable to the fact that for dialysis therapy in Japan, ultra-pure dialysis fluids and highor super high-flux dialyzers with excellent biocompatibility are frequently used, which ensure the quality of dialysis to be satisfactory.…”
Section: Discussionmentioning
confidence: 92%
“…Caffeine, alcohol, antidepressants other than bupropion, antipsychotics, antiemetics, dopamine blockers, are centrally acting antihistamines. However, other studies show that cigarette smoking and coffee drinking is not related to RLS causes [ 16 ].…”
Section: Reviewmentioning
confidence: 99%